2022
DOI: 10.1021/acs.energyfuels.2c03395
|View full text |Cite
|
Sign up to set email alerts
|

Insight into Water Occurrence and Pore Size Distribution by Nuclear Magnetic Resonance in Marine Shale Reservoirs, Southern China

Abstract: The exploitation of shale gas has been a hot topic, and the understanding of water occurrence and pore size distribution in shale reservoirs plays a crucial role in efficiently developing this type of resource. In this study, we target moderate-shallow marine shales from the Lower Cambrian Niutitang Formation and deep marine shales from the Lower Silurian Longmaxi Formation. Low-field nuclear magnetic resonance is applied to investigate the water occurrence and pore size distribution together with complementar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 35 publications
0
26
0
Order By: Relevance
“…Due to the complexity of the pore structure of the actual shale reservoir, it is difficult for the nanoscale simulations to accurately characterize the imbibition law in a shale nanopore-fracture system. 63 Further study of the imbibition patterns within the pore network on the basis of nanoscale achievements provides a clearer understanding of the oil− water transport characteristics at the multiscale level.…”
Section: Imbibition Mechanisms In Shale Pore Networkmentioning
confidence: 99%
“…Due to the complexity of the pore structure of the actual shale reservoir, it is difficult for the nanoscale simulations to accurately characterize the imbibition law in a shale nanopore-fracture system. 63 Further study of the imbibition patterns within the pore network on the basis of nanoscale achievements provides a clearer understanding of the oil− water transport characteristics at the multiscale level.…”
Section: Imbibition Mechanisms In Shale Pore Networkmentioning
confidence: 99%
“…For conventional reservoirs, the minimum miscible pressure (MMP) between CO 2 and oil can be measured by slim-tube, rapid pressure increment, vanishing IFT, rising-bubble apparatus, sonic response, NMR, and computed tomography (CT) methods . For example, NMR is applied to study multiphase fluid transport in porous media by measuring the transverse relaxation time T 2 of hydrogen nuclei in a magnetic field. , Li et al measured the transverse relaxation time of hydrocarbons at different CO 2 injection pressures using NMR. They found that the transverse relaxation time of hydrogen nuclei in hydrocarbons decreases with the CO 2 injection pressure increasing.…”
Section: Mass Transfer Between Co2 and Oil At The Nanoscalementioning
confidence: 99%
“…67 For example, NMR is applied to study multiphase fluid transport in porous media by measuring the transverse relaxation time T 2 of hydrogen nuclei in a magnetic field. 68,69 Li et al 70 measured the transverse relaxation time of hydrocarbons at different CO 2 injection pressures using NMR. They found that the transverse relaxation time of hydrogen nuclei in hydrocarbons decreases with the CO 2 injection pressure increasing.…”
Section: Interfacial Tension Between Co 2 Andmentioning
confidence: 99%
“…NA can characterize the specific area, average pore diameter, and pore volume of mesopores, while MIP can get the pore-throat size distribution from the nano to micro scale, based on which, the tortuosity can be calculated. The pore parameters extracted from NA and MIP can be used to analyze the controlling factors of irreducible water saturation. Nuclear magnetic resonance (NMR) is a significant technique to investigate water occurrence, which when associated with a high-speed centrifugation machine can distinguish the pore size distribution of movable and irreducible liquid. The principle of NMR is based on the fact that liquid in large pores has a longer relaxation time, and liquid in small pores has a short relaxation time. Thus, the whole pore size distribution can be obtained. NMR T 2 relaxation time can only reflect the pore size distribution, but the real pore size can be obtained by a converting factor, which can convert the T 2 value into the real pore size .…”
Section: Introductionmentioning
confidence: 99%